The Influence of J-Pop Music on Teenagers Emotions at the Chibicon Surabaya Event - Puspita kharisma ayu; Sadhana, Senyum (Solah, 2025)
The J-Pop music phenomenon among Surabaya teenagers shows a high level of consumption, both in the form of music, music videos (MVs), and merchandise. J-Pop music generally presents positive messages and arrangements, so it can significantly influence the emotional state of teenagers. The most dominant effects include feelings of joy, enthusiasm, and optimism. In addition, J-Pop MVs are packaged with a distinctive visual style such as anime and various colours, which also strengthens this positive emotional experience. This study uses a descriptive qualitative approach involving 100 teenagers who attended the Chibicon event in Surabaya as a sample. The results of this study indicate that J-Pop music consumption contributes to improved mood and emotional regulation which is healthier for teenagers.